Robust fractional adaptive control based on the strictly positive realness condition - Ladaci, Samir; Charef, Abdelfettah; Loiseau, Jean Jacques (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a new approach to robust adaptive control, using fractional order systems as parallel feedforward in the adaptation loop. The problem is that adaptive control systems may diverge when confronted with finite sensor and actuator dynamics, or with parasitic disturbances. One of the classical robust adaptive control solutions to these problems makes use of parallel feedforward and simplified adaptive controllers based on the concept of positive realness.
Keywords: positive realness; robust adaptive control; fractional adaptive control; model reference adaptive control; feedforward; fractional calculus